If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5)(x + -5) + -12 = 5(3x + 3) + 60 Reorder the terms: 3(5 + x)(x + -5) + -12 = 5(3x + 3) + 60 Reorder the terms: 3(5 + x)(-5 + x) + -12 = 5(3x + 3) + 60 Multiply (5 + x) * (-5 + x) 3(5(-5 + x) + x(-5 + x)) + -12 = 5(3x + 3) + 60 3((-5 * 5 + x * 5) + x(-5 + x)) + -12 = 5(3x + 3) + 60 3((-25 + 5x) + x(-5 + x)) + -12 = 5(3x + 3) + 60 3(-25 + 5x + (-5 * x + x * x)) + -12 = 5(3x + 3) + 60 3(-25 + 5x + (-5x + x2)) + -12 = 5(3x + 3) + 60 Combine like terms: 5x + -5x = 0 3(-25 + 0 + x2) + -12 = 5(3x + 3) + 60 3(-25 + x2) + -12 = 5(3x + 3) + 60 (-25 * 3 + x2 * 3) + -12 = 5(3x + 3) + 60 (-75 + 3x2) + -12 = 5(3x + 3) + 60 Reorder the terms: -75 + -12 + 3x2 = 5(3x + 3) + 60 Combine like terms: -75 + -12 = -87 -87 + 3x2 = 5(3x + 3) + 60 Reorder the terms: -87 + 3x2 = 5(3 + 3x) + 60 -87 + 3x2 = (3 * 5 + 3x * 5) + 60 -87 + 3x2 = (15 + 15x) + 60 Reorder the terms: -87 + 3x2 = 15 + 60 + 15x Combine like terms: 15 + 60 = 75 -87 + 3x2 = 75 + 15x Solving -87 + 3x2 = 75 + 15x Solving for variable 'x'. Reorder the terms: -87 + -75 + -15x + 3x2 = 75 + 15x + -75 + -15x Combine like terms: -87 + -75 = -162 -162 + -15x + 3x2 = 75 + 15x + -75 + -15x Reorder the terms: -162 + -15x + 3x2 = 75 + -75 + 15x + -15x Combine like terms: 75 + -75 = 0 -162 + -15x + 3x2 = 0 + 15x + -15x -162 + -15x + 3x2 = 15x + -15x Combine like terms: 15x + -15x = 0 -162 + -15x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-54 + -5x + x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-54 + -5x + x2)' equal to zero and attempt to solve: Simplifying -54 + -5x + x2 = 0 Solving -54 + -5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '54' to each side of the equation. -54 + -5x + 54 + x2 = 0 + 54 Reorder the terms: -54 + 54 + -5x + x2 = 0 + 54 Combine like terms: -54 + 54 = 0 0 + -5x + x2 = 0 + 54 -5x + x2 = 0 + 54 Combine like terms: 0 + 54 = 54 -5x + x2 = 54 The x term is -5x. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5x + 6.25 + x2 = 54 + 6.25 Reorder the terms: 6.25 + -5x + x2 = 54 + 6.25 Combine like terms: 54 + 6.25 = 60.25 6.25 + -5x + x2 = 60.25 Factor a perfect square on the left side: (x + -2.5)(x + -2.5) = 60.25 Calculate the square root of the right side: 7.762087348 Break this problem into two subproblems by setting (x + -2.5) equal to 7.762087348 and -7.762087348.Subproblem 1
x + -2.5 = 7.762087348 Simplifying x + -2.5 = 7.762087348 Reorder the terms: -2.5 + x = 7.762087348 Solving -2.5 + x = 7.762087348 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 7.762087348 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 7.762087348 + 2.5 x = 7.762087348 + 2.5 Combine like terms: 7.762087348 + 2.5 = 10.262087348 x = 10.262087348 Simplifying x = 10.262087348Subproblem 2
x + -2.5 = -7.762087348 Simplifying x + -2.5 = -7.762087348 Reorder the terms: -2.5 + x = -7.762087348 Solving -2.5 + x = -7.762087348 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -7.762087348 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -7.762087348 + 2.5 x = -7.762087348 + 2.5 Combine like terms: -7.762087348 + 2.5 = -5.262087348 x = -5.262087348 Simplifying x = -5.262087348Solution
The solution to the problem is based on the solutions from the subproblems. x = {10.262087348, -5.262087348}Solution
x = {10.262087348, -5.262087348}
| 3x^2-12+7=0 | | 9a^2-17a=2 | | -16t^2+75t+5=0 | | 66t^2+79t+5=0 | | w(3w+1)(w+15)=0 | | 36t^2+79t+5=0 | | 3w(w-4)=-9 | | (w-11)(w-4)=-10 | | 7a=2(a-20)+30 | | X^2-72x+1152=0 | | 0,5x+3=-10,5 | | 10x+28=6x+72 | | 171-3x=42x+16 | | 1,2x+3=-11,2 | | 6+2i/9-3i | | -9/4d+1=4/d+1 | | -8-4x=-7-9x | | 1/12d-4/3d=15 | | 1/12d-4/3d | | 1/12d-4/3d=y | | X^2-64x+962=0 | | 5y/6-2y/3+5=y | | X^2-64x-962=0 | | 7m^2+9m+5=0 | | -37(14x)+28(21x)=72-72+-166+96 | | (7+2i)/(3-3i) | | 4(x-4)+2x-3=4(4-x) | | 3n^2=-10n-4 | | 16y-5+2y=70 | | ((6x+18)/(5x^2))/((6x^3)/(25)) | | X^2-60x+960=0 | | x^2+15x=450 |